Estrategias de desarrollo cultural en las escuelas. La expresión oral de los estudiantes de bachillerato en la Institución Educativa “11 de Marzo” durante el año lectivo 2020 como ámbito etnolingüístico de desarrollo - Velasteguí Angulo, Verónica Marcela (2020)
The present investigation was carried out in the Fiscal Educational Institution "March 11" of the city of Quito, with third year high school students. An observational analysis was carried out that produced the diagnosis of problems that students presented at the time of executing the communication process, showing a difficulty when expressing their thoughts, ideas and points of view, such as: lack of vocabulary, barbarism and stage fright. This problem leads to raise the questions: How can oral expression seen as a communicative ability contribute to the debate and orientation of cultural strategies that, based on ethnolinguistics, facilitate local development in the Quito canton? What strategies can be used to eradicate this problem in students and achieve local and personal development? In order to determine the way in which oral expression can contribute to the debate and orientation of cultural strategies that, based on ethnolinguistics, facilitate the local development of the Quito canton with third-year high school students of the Educational Institution "11 de Marzo" as actors in the local development process. The epistemological foundations taken for this research are: Speranza, A., Dell Hymes and Coseriu, E. express their position regarding the importance of Ethnolinguistics and language as a verbal communication tool based on oral expression. Based on this, a pedagogical proposal was designed that includes technological tools as a methodological process in the proper management of communication, through oral skills linked to ethnolinguistics. In addition, the strategies proposed based on the needs presented by the students, to achieve meaningful learning, through motivation and a genuine commitment in the behavior of the students when carrying out the oral expression process, apart from them the passive attitude that was initially evidenced